Antiviral Activity of Crude Hydroethanolic Extract from Schinus terebinthifolia against Herpes simplex Virus Type 1 - Nocchi, Samara Requena; Companhoni, Mychelle Vianna Pereira; de Mello, João Carlos Palazzo; Dias Filho, Benedito Prado; Nakamura, Celso Vataru; Carollo, Carlos Alexandre; Silva, Denise Brentan; Ueda-Nakamura, Tânia (Planta Medica, 2017)
Herpes simplex virus infections persist throughout the lifetime of the host and affect more than 80 % of the humans worldwide. The intensive use of available therapeutic drugs has led to undesirable effects, such as drug-resistant strains, prompting the search for new antiherpetic agents. Although diverse bioactivities have been identified in Schinus terebinthifolia, its antiviral activity has not attracted much attention. The present study evaluated the antiherpetic effects of a crude hydroethanolic extract from the stem bark of S. terebinthifolia against Herpes simplex virus type 1 in vitro and in vivo as well as its genotoxicity in bone marrow in mammals and established the chemical composition of the crude hydroethanolic extract based on liquid chromatography-diode array detector-mass spectrometry and MS/MS. The crude hydroethanolic extract inhibited all of the tested Herpes simplex virus type 1 strains in vitro and was effective in the attachment and penetration stages, and showed virucidal activity, which was confirmed by transmission electron microscopy. The micronucleus test showed that the crude hydroethanolic extract had no genotoxic effect at the concentrations tested. The crude hydroethanolic extract afforded protection against lesions that were caused by Herpes simplex virus type 1 in vivo. Liquid chromatography-diode array detector-mass spectrometry and MS/MS identified 25 substances, which are condensed tannins mainly produced by a B-type linkage and prodelphinidin and procyanidin units.
Keywords: HSV-1; antiherpetic effects; mode of antiviral action; Schinus terebinthifolia; Anacardiaceae; LC-DAD-MS; condensed tannins